“UNCONSCIONABLE ABUSE” – SECTION 20(9) OF THE COMPANIES ACT 71 OF 2008 Ex Parte Gore NNO 2013 (3) SA 382 (WCC) - Darren Subramanien (Obiter, 2014)
The remedy provided for in company law of “piercing of the corporate veil” was a remedy that only existed in the common law but has now been expressly incorporated into legislation under the Companies Act 71 of 2008. The “piercing of the corporate veil” statutory provision is contained in section 20 (9) of the Act. This provision does raise an important question as to how the courts will interpret the term “unconscionable abuse”. The term “unconscionable abuse” is not defined in the Act and the section fails to provide any guidance on the facts or circumstances that would constitute an “unconscionable abuse” of the separate juristic personality of the company. This paper discusses the interpretation of the term “unconscionable abuse” in light of the judgment in Ex parte Gore NNO (2013 (3) SA 382 (WCC)) and seeks to provide clarity with regard to the implication of section 20(9) of the Act on the common-law grounds of piercing the corporate veil.